Annual Update in Intensive Care and Emergency Medicine 2017 - Vincent, Jean-Louis (Springer International Publishing : Imprint: Springer, 2017)
The Annual Update compiles reviews of the most recent developments in experimental and clinical intensive care and emergency medicine research and practice in one comprehensive reference book. The chapters are written by well recognized experts in these fields. The book is addressed to everyone involved in internal medicine, anesthesia, surgery, pediatrics, intensive care and emergency medicine.
Keywords: Medicine.; Emergency medicine.; Critical care medicine.; Internal medicine.; elektronické knihy; electronic books